Assessment of chemotherapy-induced febrile neutropenia in cancer patients - Malona Lilly Philip; Neethu Saj; Antony Mathew Sebastian; Uday Venkat Mateti; Vijith Shetty (Indian Journal of Medical and Paediatric Oncology)
Purpose: Chemotherapy-induced febrile neutropenia (CIFN) is an adverse drug reaction which needs medical attention. The treatment options for the CIFN are mandatory to improve treatment outcomes and quality of life. Methods: A prospective observational study was conducted in the in-patients and out-patients of oncology department who received chemotherapy from October 2016 to March 2017. The information such as demographics (age, gender, and comorbidities), complaints on admission, hematological investigations (neutrophil counts, platelet counts, hemoglobin levels, erythrocyte sedimentation rate, and white blood cells), type of tumor, stage of cancer, prophylaxis, cycle of antineoplastic chemotherapy that cause febrile neutropenia, treatment history, and outcome data were obtained from the patient's clinical record. The Multinational Association for Supportive Care in Cancer score and Absolute Neutrophil Count grading was used to predict the patient's risk of developing CIFN. Results: Out of 200 patients, 19 patients developed 22 episodes of CIFN. The overall occurrence of CIFN during the study was 9.5%. The higher incidence of CIFN has been observed among male gender (57.89%), stage III patients (42.10%), solid tumor (73.68%), and double chemotherapy regimen (59.1%). The higher incidence of CIFN was developed in I cycle (36.36%) followed by II cycle (22.72%) and VI cycle (18.18%). Conclusions: The incidence of CIFN during the study was 9.5%. In the 19 chemotherapy-induced FN patients, there has no significant effect of prophylaxis to prevent the febrile neutropenia.